2016
DOI: 10.1038/srep35501
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Loci Analysis Reveals Post-bottleneck Recovery of Genetic Diversity in the Tibetan Antelope

Abstract: The Tibetan antelope (chiru, Pantholops hodgsoni) is one of the most endangered mammals native to the Qinghai-Tibetan Plateau. The population size has rapidly declined over the last century due to illegal hunting and habitat damage. In the past 10 years, the population has reportedly been expanding due to conservation efforts. Several lines of evidence suggest that the Tibetan antelope has undergone a demographic bottleneck. However, the consequences of the bottleneck on genetic diversity and the post-bottlene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…()* of STR loci was 0.7767 and 0.8446 for the within and among-deme studies respectively. Our results are consistent with previous studies (Du et al, 2016;F. Zhang, Jiang, Xu, Zeng, & Li, 2013).…”
Section: Tibetan Antelope Maintained High Genetic Diversity After a Hsupporting
confidence: 94%
See 1 more Smart Citation
“…()* of STR loci was 0.7767 and 0.8446 for the within and among-deme studies respectively. Our results are consistent with previous studies (Du et al, 2016;F. Zhang, Jiang, Xu, Zeng, & Li, 2013).…”
Section: Tibetan Antelope Maintained High Genetic Diversity After a Hsupporting
confidence: 94%
“…Previous studies suggested that Tibetan antelope populations maintained high genetic variation with no signs of population structure (Ahmad et al, 2016;Du et al, 2016;H. Zhou, Li, Zhang, Yang, & Liu, 2007), although the genetic effects of the population crash on Tibetan antelope remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Estimating and evaluating genetic variation is critical for the effective evaluation and management of endangered populations and species (Caniglia, Fabbri, Galaverni, Milanesi, & Randi, ; Du et al, ; Wang et al, ). Populations with higher genetic diversity are often inferred to have greater capacity to adapt to environmental change (Frankham, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no reports on the genetic structure of S. marmoratus populations that cover most of the habitat, from Japan to China. Microsatellite markers used in the exploration of population genetic structure usually exhibit co‐dominant inheritance and high diversity, with relatively modest analysis expense (Chong & Roe, ; Du et al, ; Kitson‐Walters et al, ). This study aimed to draw a comprehensive picture of the patterns of genetic diversity and structure along the distribution area in the coastal waters of the northwestern Pacific, across a large latitudinal range, using microsatellite markers.…”
Section: Introductionmentioning
confidence: 99%